General practitioners' views on perceived and actual gains, benefits and barriers associated with the implementation of an Australian health assessment for people with intellectual disability. (10th July 2012) - Lennox, N. G.; Brolan, C. E.; Dean, J.; Ware, R. S.; Boyle, F. M.; Taylor Gomez, M.; van Dooren, K.; Bain, C.
Abstract: Background  Health assessments for people with intellectual disability have been implemented in the UK, New Zealand and Australia, and have led to improved health outcomes. The Comprehensive Health Assessment Program (CHAP) has been shown to improve the health of people with intellectual disability. Similar to other health assessments, it is designed to address healthcare needs, many of which are often overlooked in this population, through better communication between the general practitioner (GP), support worker and the person with intellectual disability. This study investigates GP views of the perceived and actual benefits, gains and barriers associated with its uptake and use in practice. Method  As part of a larger randomised controlled trial of the CHAP, 46 GPs in Queensland, Australia, completed two telephone interviews that included open‐ended questions about their perceptions of the health assessment. The GPs were enrolled in the intervention arm of the trial. Interviews took place at commencement and conclusion of the trial to gain the views of GPs as they experienced using the CHAP. Thematic analysis was used to identify key themes and patterns from the GP responses. Results  Four themes were identified: better healthcare and uncertain benefits captured GP perceptions of the potential gains associated with use of the CHAP, while two further themes, organisational barriers in the general practice setting and engagement across the healthcare triad highlighted strengths and barriers related to implementation. Anticipated concerns about time raised by GPs at commencement of the trial were borne out in practice, but concerns about communication and cooperation of people with disabilities were not. Matters associated with support worker engagement emerged as an area of concern. Conclusions  GPs perceive the CHAP as a structured and comprehensive approach to the detection of medical problems as well as an aid in overcoming communication barriers between the doctor and the person with disability. Our findings suggest that some GPs may find it difficult to predict the benefits of using health assessments such as the CHAP. Achieving optimal uptake is likely to require attention at policy and systems levels to address: GP time constraints in providing healthcare to this population; enhancement of support worker training and organisational structures to encourage comprehensive health assessment and follow‐up activities; and GP awareness of the improved health outcomes shown to derive from the use of comprehensive health assessments.